Progress on the role of N-acetyltransferase 10 in tumor development - GU Zhongjia, LAI Siying, CHEN Dunjin, DU Lili (Jichu yixue yu linchuang)
N-acetyltransferase10(NAT10) is a protein widely expressed in a variety of tissues and cells. The high expression of NAT10 is closely related to tumor invasion, metastasis and drug resistance. The mechanism of NAT10 promoting tumor genesis and development involves the regulation of cell cycle, mRNA stability, translation efficiency and related pathways due to the changes in the expression or location of NAT10, thus affecting the occurrence, development and prognosis of tumors.